An investigation of revenue collection from tenants: a case study of the department of Public Works, Mashonaland East Province - Shamuyarira, Judith (Midlands State University, 2018)
This research focused on investigation on revenue collection from tenants using a case study of the Department of Public Works, Mashonaland East Province from 2009 to 2013. The researcher mainly used the primary data extracted by the use of questionnaires and Interviews Results of the study show that procedures used by the department in selecting lessees were not uniform as the department did not have standing, documented and systematic policy in place. The study also highlighted on the factors leading to escalation of outstanding rental revenue. Having analyzed all the factors, the greatest of them all was inadequate screening of prospective tenants by the department. The issue on trends in outstanding rental revenue was highlighted by the researcher. The only action taken by the department on defaulting tenants was by means of negotiations. Measures were non-existent for defaulting tenants and the tenants ended up having a culture of nonpayment of rentals. This prejudiced the Department of regular monthly rental income. The researcher recommends that the Department comes up with a documented and systematic evaluation policy that is uniformly applied to every prospective lessee.